BIO-PROSPECTING OF CLEISTANTHUS COLLINUS AND ITS ANTIBACTERIAL ACTIVITY - Suman.T; Elangomathavan, R. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: This present study was planned to resolve the phytochemical profile of the plant leaf extracts prepared by two different (hot and cold) extraction methods and to determine the bactericidal efficiency of Cleistanthus collinus. Methods: Preliminary phytochemical analysis of C. collinus leaf crude extracts (methanol, ethanol, ethyl acetate and aqueous) were performed according to the Odebiyi method. The bactericidal efficiency of C. collinus leaf crude extracts were tested by standard microbiological methods against Escherichia coli, Salmonella typhi, Klebsiella pneumoniae, Pseudomonas aeruginosa (Gram-negative) and Staphylococcus aureus, Listeria monocytogenes (Gram-positive). Results: The presence of secondary metabolites like alkaloids, flavonoids, steroids, terpenoids, tannins, phlobatannins, glycosides and saponins were observed in preliminary phytochemical analysis of C. collinus leaf crude extracts. Analysis of bactericidal efficiency for the various solvent based extracts revealed that methanol extract of C. collinus was found to be intensive antibacterial activity [> 18 mm inhibition zone; MIC (0.27 - 0.42 mg/ml); MBC (0.35 â€“ 0.50 mg/ml)] which is followed by ethanol extract and other extracts. Â  Conclusion: From this study, it is obvious that the C. collinus leaf crude extract could be exploited for the preparation of new and efficient green medicine to treat various infectious diseases for both human being and veterinary animals. Keywords: Cleistanthus collinus, Phytochemistry, Bioprospecting, Antibacterial activity, MIC, MBC.